Sexualized drug use and its association with sexual health among men who have sex with men in Cyprus - Antonios Poulios; Stavroula Triantafyllidou; Anna Apostolidou; Christos Krasidis; Ivonne Valdez Paez Petrou; Evi Kyprianou; Ioanna Yiasemi; Anna Papadaki; Christos Minas; Georgios Nikolopoulos; Chrysanthos Georgiou (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας)
Sexualised drug use (SDU) i.e., the use of psychoactive substances in a sexual context, has been becoming the focus of researchers’ interest over the past years. This is due to SDU's rising popularity, especially among the LGBTQI+ people and its impact on sexual and overall health of people engaging in it. SDU’s frequency in Europe, including Greece, and Middle East among men who have sex with men (MSM) is reported to be as high as 26.7% to 51%. Our aim was to examine SDU in regard to the demographics and sexual health of MSM in Cyprus. 460 MSM, with mean age 31.2 (SD=9.1), completed an online questionnaire, which included questions on human immunodeficiency virus (HIV) status, Sexually Transmitted Infections (STIs) diagnoses, condom use, Post Exposure Prophylaxis (PEP) and Pre-Exposure Prophylaxis (PrEP), frequency of SDU, number of sexual partners, and polydrug use. SDU was reported by 46.7% (215) of the participants and was predicted by age, HIV status, and the number of sexual partners. MSM in Cyprus report high rates of SDU, which is related to sexual health-related variables. Further research should focus on patterns of use, impact and needs of people engaging in “chemsex” specifically. Healthcare professionals in Cyprus should have adequate interdisciplinary training in SDU, that is, the effects, harm reduction and therapeutic approach regarding the specific substances used, as well as the overall challenges, such as sexual inhibition, minority stress and probable HIV stigma people engaging in SDU deal with.